Drought and flood risk mapping using a GIS-based multi-criteria decision method: A case of the Olifants Basin, South Africa - Luxon Nhamo; James Magidi; Sylvester Mpandeli; Onisimo Mutanga; Stanley Liphadzi; Tafadzwanashe Mabhaudhi (Next Sustainability)
Droughts and floods are climate extremes of the same hydrological cycle that need to be studied concurrently. In this age of increasing climate risks and uncertainty, droughts and floods have become the most impactful extreme climate events accounting for about 80 % of loss of human life and 70 % of economic losses in sub-Saharan Africa alone. However, research has tended to study the two climate extremes in isolation. In this study, the Analytic Hierarchy Process (AHP), a Multi-criteria Decision Method (MCDM), together with Geographic Information System (GIS) and geostatistical techniques were used to simultaneously detect and assess drought and flood risks in the Olifants River Basin in South Africa. The drought and flood risk maps were delineated and overlaid on the smallest water management units to identify sub-basins at risk of either drought or flooding. Results indicate that low-lying areas are at risk of floods but can resist drought conditions for long periods as water accumulation allows the soils to retain water for prolonged periods. Whereas high-altitude areas quickly show drought stress as the shallow soils on steep slopes are incapable of retaining water for longer periods but are generally at low risk of floods. The mapped drought and flood risk areas agree with historical and topographic data, and satellite-derived indices related to drought and floods. Understanding the close interactions between drought and floods informs inclusive and holistic strategic policy decisions on disaster risk reduction by enhancing preparedness and proactive interventions to these weather extremes.